"PSEUDOCYCLICITY" AS A RESULT OF RANDOM EVENTS WITH REFERENCE TO THE RHYTHMIC LAYERING OF MAGMATIC COMPLEXES - Yaroshevskii A.A. (My University, 2007)
The possible causes of and mechanisms forming rhythmic layering in magmatic complexes remain largely obscure. It is hardly reasonable to search for the reasons of rhythmic rock alternations among variations in external factors relative to the magmatic chamber, including additional magma injections, which should have always occurred at the right place at the right time in the course of systematic melt fractionation in magmatic chambers: rhythmic layering is too typical of differentiated complexes, and its tendencies and relations (such as the compositional variations of the rocks and minerals) are too strongly correlated with the laws of crystallization fractionation, to have always and everywhere external driving forces, which are independent of processes in the magmatic chamber itself. The problem is thus formulated as finding such characteristics of the magmatic system itself and such a character of processes in the chamber that should inevitably result in periodical oscillating character of the solidification process. It is also senseless to call upon self-organization or similar structure-forming processes (even with reference to the fundamentals of the thermodynamics of irreversible processes developed by I. Prigogine), because nobody has ever outlined any specific interactions between the structural elements of the systems that would have brought about such spatial structuring.